Strategi Komunikasi Badan Penanggulangan Bencana Daerah Kota Padang Dalam Mensosialisasikan Siaga Bencana Banjir - Irawan, Lidzikri Hendiyan; ., Defhany (CV. ITTC INDONESIA, 2023)
For an institution, including an institution that carries out outreach, a strategy is needed in the communication process because to achieve goals, systematic and directed steps are needed so that goals can be achieved. This study aims to find out how the Padang City BPBD communication strategy is in Socializing Flood Disaster Management in Padang City. This research uses a type of descriptive qualitative research. This research was conducted at the Padang City Regional Disaster Management Agency office. In this study, researchers had key informants and supporting informants. This study used 4 data collection techniques, namely interview techniques, observation, documentation, and literature study. The results of this study indicate that the Padang City BPBD communication strategy in disseminating disaster management uses several communication strategies. Among the communication strategies used are Collaborative, Informative, Interpersonal, and Inclusive Communication Strategies.